Carbon-Coated Li4Ti5O12 as Anode Material for Sodium-Ion Batteries - Lee, Yongho; Kim, Dong-Won; Lee, Joong Kee; Choi, Wonchang (AMER SCIENTIFIC PUBLISHERS, 2015)
The surface-coating of carbon was performed on the spinel Li4Ti5O12 materials for the electrochemical sodium insertion in sodium ion battery application. The carbon-coated Li4Ti5O12 was synthesized by using the citric acid sol gel method. Carbon-coated Li4Ti5O12 exhibits superior cycle performance as well as the rate capability in comparison to the pristine Li4Ti5O12. Electrochemical impedance spectroscopy analyses also reveal that surface modification with carbon suppresses the increase in resistance concerning charge transfer reaction as well as solid electrolyte interface layer formation during cycle test.
Keywords: RATE ELECTRODE MATERIAL; NEGATIVE ELECTRODE; LITHIUM; INSERTION